Antibiotics in acute exacerbations of chronic obstructive pulmonary disease. Issue 2 (26th February 2004) - Murphy, Ross; McKechnie, Martin; Dunning, Joel
Abstract : A short cut review was carried out to establish whether antibiotics improve recovery in patients with acute exacerbations of COPD. Altogether 200 papers were found using the reported search, of which four presented the best evidence to answer the clinical question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results, and study weaknesses of these best papers are tabulated. A clinical bottom line is stated